MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN COOPERATIVE LEARNING MODEL JIGSAW DI SEKOLAH DASAR - Nursyakiyah, Nursyakiyah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research begin from elementary school,because student in elementary school had difficult to understand about social science concept.This problem because of the teacher used speech method and teacher can’t improve students desire to study,so student had difficult to understand in teaching social science and make students boring to study,this research used cualitative and cuantitave approach with used cooperative learning jigsaw method in social science study.Based on research with used cooperative learning jigsaw method.Evaluation about RPP cycle assessment meeting I 71.42% I, 75% II meeting, Cycle II meeting I 89.28%, 96.43% II meeting. Assessment activity cycle teachers I encounter I 72.2%, 78.78% II meeting, meeting the second cycle I 88.88%, 91.66% II meeting. Student activity meeting I 63.90%, 67.67% II meeting, meeting the second cycle I 80.55%, 83.33% II meeting. Study results In the first cycle I mean meeting learning outcomes 59.55, meeting II average 64.61 learning outcomes. then the action for the second cycle I mean meeting learning outcomes 72.56, while in the second meeting of the average learning outcomes 79.71.  Keyword:   Hasil Belajar; Pendekatan cooperative learning model jigsaw;siswa SD